Wear behavior and subsurface layer work hardening mechanism of Fe-24.1Mn-1.21C-0.48Si steel. (2017) - Cai, Changhong; Song, Renbo; Liu, Shuai; Feng, Yifan; Pei, Zhongzheng
Abstract: The wear tests of Fe-24.1Mn-1.21C-0.48Si austenitic ultra-high manganese steel under different impact energies were carried out by using MLD-10 impact abrasive wear tester. Results showed that after impact abrasive wear, severe plastic deformation occurred and it was inhomogeneous. Worn surface hardness and depth of hardening layer after impact wear increased with the increase of impact energy. The wear resistance increased with the impact energy increasing in the range of 0.5J ~ 1J and 2J ~ 4J. When the impact energy was 2J, the steel had the worst wear resistance. The work hardening mechanism also changed with the increase of impact energy. The work hardening mechanism included dislocation planner slip, high density dislocation tangle, stacking faults, crossed dislocation walls, dislocation cells and mechanical twins.